Teknik Hafalan Berantai untuk Meningkatkan Kemampuan Menghafal Surah Pendek Kelas V Madrasah Ibtidaiyah - Chusna, Puji Asmaul; Agustina, Putri; Andini, Revany Dian; Purwandari, Wahyu; Nurjannah, Nofa (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This study aims to improve the ability of fifth-grade students at Madrasah Ibtidaiyah to memorize short surahs of the Qur’an Hadith subject. Memorizing short surahs is a funtamental aspect of islamic education as it is closely related to daily worship and the development of students’ religius character. This reserch amployed a Classroom Action Reserch (CAR) apporach, carried out in two cycles consisting of planning, action, observation, and refklection. The subjesubjects werw 20 students who dad difficulties in memorizing and reciting qur’anic verses. The chain memoeization technique was implemented through repetitive group recitation and individual turns, fostering an interactive and collaborative learning environment. The result indicated a signivicant improvement and students’ memorization skills, with the class average increasing from 62,65 in the pre-cycle (66% mastery) to 75.65 in cycle I (76%) and 81,6 in cycle II (82%). In addition to quantitative gains, students also showed increased self-confidence, cocetration, and participation.The succes of this technique was akso supported by the teacher’s role as a ficilitator and parental involvement at home. Chain memorization proved to be effection and is recommended for regular use in Qur’anic learning at the elementary level.